Analisis Semiotika Charles Sanders Peirce Tentang Makna Logo Tour de Aceh - Iga Desara; Jamiati KN (Departement of Mathematics Education, 2023)
This study is entitled Semiotic Analysis of the Tour de Aceh Logo as an icon from the event organized by the Aceh Culture and Tourism Office. This event will be held for the first time in Takengon on May 14 2022 and the second stage will be held in Aceh Besar and Banda Aceh on May 16 with a total distance of 150 kilometers. This year the Tour de Aceh event will be held again on March 11-12 2023 in Banda Aceh and Aceh Besar. There are two categories of this activity that will take place, namely leisure bikes and road races. Tour de Aceh is planned to be carried out in the future with the aim as part of attracting tourist visits to Aceh, especially in the sports tourism sector. This study uses qualitative methods with Charles Sanders Pierce's semiotic analysis, semiotics uses triangles, namely objects, representations, and interpretants. The logo for the Tour de Aceh event has an implicit meaning and is unique in its own way, namely the two-dimensional format, colors and fonts. The Tour de Aceh logo contains the meaning, Nature, Culture, Brave.